The presence of the Qur’an and hadith in the films of majid majidi - Yorulmaz, Bilal (My University, 2014)
Majid Majidi is a famous Iranian director who has won many awards around the world. However, although he has won many awards, what makes Majidi a particularly interesting and important Iranian filmmaker is his presentation of Islam in his movies. Unlike other Iranian filmmakers, Majidi does not tell his audience about Islamic values; nor does he quote the Qur’an or include the sayings of the Prophet (Hadith). Nevertheless, Islam penetrates all of his films in a subtle way and to such an extent that watching a Majidi movie is like reading theQur’an. This essay will show the view of Islam Majid Majidi represents in his films and how he represents that view of Islam.
Keywords: Iranian Cinema; Majid Majidi; Islam; The Qur’an; Hadith; Religious Education